Energy Efficient D2D Communication Under Downlink Heterogeneous Network - Martinus Erico Noktafianus Hindarto; Nur Izza Rahma; Nachwan Mufti Adriansyah; Vinsensius Sigit Widhi Prabowo (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2022)
The increase in cellular users (CU) caused data traffic congestion on the Base Station (BS). Device to Device (D2D) communication can be used to reduce the traffic on BS. D2D communication is direct communication between devices without using a central BS to reduce traffic congestion. CU and D2D users will share the same Resource Block (RB), but there is a drawback that causes interference. This study employs a downlink direction Heterogeneous Network (HetNet) system model to mitigate interference issues. Resource allocation is performed using a greedy algorithm, and to enhance its performance, two small cell base stations (SB) were incorporated, denoted as SB1 (1st SB) and SB2 (2nd SB), thereby transforming the algorithm into a greedy algorithm with SB1SB2. A comparative analysis was conducted between the greedy algorithm with SB1SB2 and the conventional greedy algorithm (without the addition of SB1 and SB2). Furthermore, the authors manipulated the radius of the macro cell base station (MB) in this study to examine its impact on system performance. The results obtained from the simulation are greedy with the SB1SB2 algorithm getting a lower value on the sum data rate with a value of 1.62 Ã— 108 bps, spectral efficiency with a value of 9.02 bps/Hz, total fairness (CU and D2D) with a value of 0.4095. Meanwhile, in terms of power efficiency, the greedy algorithm with SB1SB2 has a higher value of 10.40%. However, resource allocation in both algorithms is not the best solution. So that the resulting performance parameters are less than optimal.